Analgesic and Antipyretic Effects of Red Dragon Fruit (Hylocereus polyrhizus) Peel Extract in White Male Rats - Betharia Lorenza Br Subakti; Chrismis Novalinda Ginting; Linda Chiuman (Majalah Obat Tradisional, 2022)
Red dragon fruit (Hylocereus polyrhizus) is a tropical fruit that is currently cultivated in all tropical parts of the world. It is popular to consume its fruit flesh, while the peel is often thrown away. This red dragon fruit peel (RDFPE) is known to possess lots of phytochemical compounds with multitudes of usage, amongst them as an analgesic and antipyretic. Therefore, the active compounds of RDFPE play an important role in the natural product. This study aims to observe and analyze the analgetic and antipyretic activity possessed by red dragon fruit peel. This study is an in-vivo experiment on 25 white male rats divided into five groups, in which each group receive Na CMC, acetaminophen, and the other three groups will receive three different doses of RDFPE (500 mg/kg, 750 mg/kg, and 1000 mg/kg), respectively. Acetic acid writhing and tail immersion methods were performed to induce inflammation and Brewer’s yeast injection performed induced pyrexia. In the investigation of the acetic acid writhing test, the intervention was administered before induction, and for the tail immersion test, induction was given before and after the intervention was administered. Meanwhile, in brewer’s yeast-induced pyrexia, the rectal temperature was measured before induction, 24 hours after induction, and each hour for five four after the intervention; intervention was administered 24 hours after induction. This study found that RDFPE at the dose of 750 mg/kg and 1000 mg/kg are effective as an analgesic by reducing the average writhing and delaying the tail retraction of the experiment subject and also effective as an antipyretic by reducing the elevated temperature of the experiment subject (p<0.05). This study concludes that RDFPE possesses analgesic and antipyretic activity, especially at the higher dose. Phytochemical compounds such as alkaloids and flavonoids are most likely responsible for this analgesic and antipyretic activity by inhibiting inflammation activity.